Association Between Body Mass Index (BMI) and Symptoms Severity in Patients Affected by Covid-19 in Kaski District, Nepal - Nagila, Amar; Bhattarai, Kalpana; Koirala, Reetu (Technium BioChemMed, 2021)
Coronavirus disease 2019 (COVID-19), an illness caused by a novel coronavirus called severe acute respiratory syndrome (SARS CoV-2) first broke out from China and speeded globally. The virus so far has spread to almost all countries & caused millions of deaths and infection making it a worst pandemic. The clinical characteristics of Covid-19 vary from asymptomatic to fatal. This case-control study is conducted to examine the association between body mass index (BMI) levels and the Covid-19 disease severity. A total of 400 cases, and 699 controls were taken as the sample population for this study. All the study participants underwent RT-PCR test at Life Care Diagnostics and research center. Ethical consideration for this study was taken from institutional review committee, lifecare diagnostic and research center. Consent was taken from every subject before enrolling in the study. Our findings reveal the association between BMI and Covid-19 symptoms severity in case populations. We also have an impression that individuals with high BMI and comorbidity are even more likely to be in need of a ventilator and had to be admitted in hospital for a longer interval of time with the disease severity.